2020
DOI: 10.1021/jacs.0c01883
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Opioid Monitoring along with Nerve Agents on a Wearable Microneedle Sensor Array

Abstract: There are urgent needs for sensing devices capable of distinguishing between episodes of opioid overdose and nerve agent poisoning. This work presents a wearable microneedle sensor array for minimally invasive continuous electrochemical detection of opioid (OPi) and organophosphate (OP) nerve agents on a single patch platform. The new multimodal microneedle sensor array relies on unmodified and organophosphorus hydrolase (OPH) enzyme-modified carbon paste (CP) microneedle electrodes for square wave voltammetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 28 publications
0
135
1
Order By: Relevance
“…Efforts aimed at expanding the scope of detectable analytes beyond common metabolites and electrolytes, have led to the detection of stress J o u r n a l P r e -p r o o f hormone cortisol in sweat relying on various recognition elements of bioaffinity-based (Torrente-Rodríguez et al, 2020a) and molecularly imprinted polymer (MIP)-based (Parlak et al, 2018) sensors. Additionally, several studies have reported the detection of various drugs, either therapeutic or illicit, in sweat and ISF samples (Goud et al, 2019;Mishra et al, 2020a;Tai et al, 2019Tai et al, , 2018. Add to these, the studies on utilizing the great potential of electrochemical aptamer-based sensors toward in-vivo detection of drug targets in blood samples of anesthetized animals (Arroyo-Currás et al, 2018;Dauphin-Ducharme et al, 2019).…”
Section: The Present State-of-the-art (2018-2020)mentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts aimed at expanding the scope of detectable analytes beyond common metabolites and electrolytes, have led to the detection of stress J o u r n a l P r e -p r o o f hormone cortisol in sweat relying on various recognition elements of bioaffinity-based (Torrente-Rodríguez et al, 2020a) and molecularly imprinted polymer (MIP)-based (Parlak et al, 2018) sensors. Additionally, several studies have reported the detection of various drugs, either therapeutic or illicit, in sweat and ISF samples (Goud et al, 2019;Mishra et al, 2020a;Tai et al, 2019Tai et al, , 2018. Add to these, the studies on utilizing the great potential of electrochemical aptamer-based sensors toward in-vivo detection of drug targets in blood samples of anesthetized animals (Arroyo-Currás et al, 2018;Dauphin-Ducharme et al, 2019).…”
Section: The Present State-of-the-art (2018-2020)mentioning
confidence: 99%
“…4bii). Voltammetric techniques have also been demonstrated for the sensitive detection of opioids and nerve agents (Mishra et al, 2020a), and explosives (Sempionatto et al, 2017a).…”
Section: Voltammetric Sensorsmentioning
confidence: 99%
“…There are two design strategies for fabricating in-situ microneedle sensors. The first involves the development of electroactive solid microneedles, while the second uses hollow microneedles to house conventional electrochemical sensing elements, such as modified carbon pastes and fibres 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 . The fabrication of solid microneedle sensors typically employs sputtering or e-beam evaporation to metallise polymeric or metallic microneedles to produce an electroactive surface, which is then functionalised with an appropriate enzyme or coating to selectively detect an analyte 62 .…”
Section: Microneedle Diagnostic Platformsmentioning
confidence: 99%
“…Both solid and hollow microneedle-based in-situ sensors have detected therapeutic drugs, electrolytes, alcohol, pH changes, small molecules, including glucose, nitric oxide, ascorbic acid, uric acid, dopamine, glutamate, neurotransmitters and organophosphorus nerve agents 61 , 62 , 66 , 93 , 122 , 124 , 125 , 126 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 . For solid microneedle biosensors, recognition elements such as enzymes are typically cross-linked to the microneedle surface using covalent cross-liking chemistries to protect them from accidental removal or degradation during skin application 142 .…”
Section: Microneedle Diagnostic Platformsmentioning
confidence: 99%
“…The author declares no conflict of interest. The novel approach using a wearable microneedle sensor array to distinguish between opioid overdose and nerve agent poisoning was reported in the Journal of American Chemical Society in 2020 by the same group [39]. The microneedle array was fabricated by using a hollow microneedle working electrodes allowing (i) for direct voltammetric detection of fentanyl-based on oxidative dealkylation of the piperidine tertiary amine and norfentanyl production with a peak at +0.7 V, and (ii) for square wave voltammetry of the organophosphate hydrolase-by product, i.e., p-nitrophenol using methyl paraoxon as a nerve agent simulant, with a peak at ca.…”
Section: Conflicts Of Interestmentioning
confidence: 99%